ANALISIS PEMIDANAAN PERBUATAN MERINTANGI AKTIVITAS PERTAMBANGAN MINERAL DAN BATUBARA PERSPEKTIF UNITED NATION GUIDING PRINCIPLES ON BUSINESS AND HUMAN RIGHTS DAN UUD 1945 - Siti Maemunah (JIL : Journal of Indonesian Law, 2024)
Ratification of Law no. 3 of 2020 became the new Minerba Law and the implementation of Article 162 of the Minerba Law contained there in triggered conflicts that occurred in society. Article 162 of the Mining and Coal Law is referred to as the "Penalty Article" and the "Rubber Article", this is because the substance contained therein contains criminal offenses for anyone who "obstructs" or "disrupts" mining activities. Punishment here is related to criminal acts, where criminal acts are actions that violate laws, statutes, norms and values that apply in society. The results show that the punishment for obstructing mineral and coal mining activities in Indonesia has violated the human rights of communities that refuse mining. The government is considered to have abused the people living in the area around the mining area. In the perspective of the UNGPs-BHR, the criminal act of obstructing mineral and coal mining activities is said to not fulfill the elements contained in the UNGPs-BHR.